2015
DOI: 10.1002/tcr.201500236
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Graphene-based Electrochemical Biosensors

Abstract: The detailed records and conclusions on the important advancements in graphene-based electrochemical biosensors have been reviewed. Due to their outstanding properties, graphene-based materials have been widely studied for the accurate electrochemical detection of many biomolecules, which is extremely vital to the development of biomedical instruments, clinical diagnosis, and disease treatment. This review discusses the graphene research for the effective immobilization of enzymes, including glucose oxidase, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 152 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…Graphene and its derivatives are studied for the construction of novel biosensor interface [67], which is critical for interface-based biosensors including electrochemical biosensors, electrochemiluminescent (ECL) biosensors and FET biosensor [86]. Many recent studies reported that nanocomposites based on graphene showed improved capability of combining different biomolecules, with higher surface area [87] and excellent biocompatibility [88].…”
Section: Biosensor Interfaces Based On Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Graphene and its derivatives are studied for the construction of novel biosensor interface [67], which is critical for interface-based biosensors including electrochemical biosensors, electrochemiluminescent (ECL) biosensors and FET biosensor [86]. Many recent studies reported that nanocomposites based on graphene showed improved capability of combining different biomolecules, with higher surface area [87] and excellent biocompatibility [88].…”
Section: Biosensor Interfaces Based On Graphenementioning
confidence: 99%
“…Many recent studies applied graphene-related materials as excellent carriers for the construction of novel nanocomposites for biosensor signal amplification [122124]. These graphene-based composites were developed by combining graphene or its derivates with metal oxides, metal nanoparticles, or conductive polymers, etc., and this kind of composites showed unique catalytic/chemical activity [86], that has been widely applied in PC biosensors [125].…”
Section: Graphene-based Composites For Signal-amplificationmentioning
confidence: 99%
“…Graphene paper displayed outstanding physical and electrochemical properties, such as high conductivity, large surface area, abundant defect sites, superior electrocatalytic activity and fast electron transfer rate, hence various enzyme biosensors based on this attractive material have been fabricated recently [11,95]. We have successfully fabricated graphene paper doped with chemically compatible PBNPs as a nanohybrid electrocatalyst [36].…”
Section: Enzyme-graphene Paper Sensorsmentioning
confidence: 99%
“…In the past two decades, intensive research and development of electrochemical sensors have enabled to fabricate different types of devices. After the development of many successful commercial devices [7][8][9][10][11]. As outlined below, several crucial methods have been developed to assemble the layered structure of graphene papers.…”
Section: Introductionmentioning
confidence: 99%
“…The first glucose oxidase (GOx) electrode was developed in 1962. 1 Since then, a wide variety of electrode materials have been reported for glucose sensors including polymers, 2 sol-gel, 3 mesoporous silica, 4 metal nanoparticles, 5 carbon nanotubes 6 and graphene-based nanomaterials. 7,8 Glucose oxidase has been recognized as an enzyme for monitoring glucose.…”
mentioning
confidence: 99%